THE INFLUENCE OF MARKETING MIX AND SERVICE QUALITY ON OUTPATIENT SATISFACTION AND LOYALTY - Syamsul, Rahmah Aulia; AP, A Rizki Amelia; Rusydi, Arni Risqiani (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Increasing competition in healthcare services requires health facilities to improve service quality and implement effective marketing strategies to sustain service utilization. Patient satisfaction and loyalty are essential indicators because they influence revisit intentions and the long-term sustainability of healthcare institutions. This study aimed to analyze the influence of the marketing mix and service quality on outpatient satisfaction and loyalty at Asinua Health Center, Konawe Regency, Southeast Sulawesi. This study employed a quantitative approach with a cross-sectional design. The research was conducted in December 2025 at the Asinua Health Center involving 128 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using univariate analysis, bivariate analysis with the Chi-Square test, and multivariate analysis using Structural Equation Modeling–Partial Least Square (SEM-PLS) through SmartPLS software. The results showed that most respondents perceived the marketing mix and service quality variables as good. Bivariate analysis indicated that most independent variables were significantly associated with patient satisfaction and loyalty (p < 0.05), except for price and place variables which showed no significant association with patient satisfaction (p > 0.05). Multivariate analysis demonstrated that all independent variables, including product, price, promotion, place, process, tangibles, empathy, reliability, responsiveness, and assurance, had a significant influence on both patient satisfaction and patient loyalty (p < 0.05). The marketing mix and service quality significantly influence outpatient satisfaction and loyalty. Improving service quality and implementing effective marketing strategies are essential to enhance patient satisfaction and strengthen patient loyalty toward healthcare facilities.